zy-dm=ky/t for y

Discussion in 'Calculator Requests' started by math_celebrity, Jul 9, 2019.

  1. math_celebrity

    math_celebrity Administrator Staff Member

    zy-dm=ky/t for y

    Isolate terms with y to solve this literal equation.

    Subtract zy from each side:
    zy - dm - zy = ky/t - zy

    Cancel the zy terms on the left side, we get:
    -dm = ky/t - zy

    Factor out y:
    y(k/t - z) = -dm

    Divide each side by (k/t - z)
    y = -dm/(k/t - z)

    (k/t - z) can be rewritten as (k - tz)/t

    We multiply -dm by the reciprocal of this quotient to get our simplified literal equation:
    y = -dmt/(k - tz)

Share This Page